Pancreatoduodenectomy with colon resection for pancreatic cancer: a systematic review - Solaini, Leonardo; de Rooij, Thijs; Marsman, E. Madelief; te Riele, Wouter W.; Tanis, Pieter J.; van Gulik, Thomas M.; Gouma, Dirk J.; Bhayani, Neal H.; Hackert, Thilo; Busch, Olivier R.; Besselink, Marc G. (HPB, 2018)
Background - Radical resection of advanced pancreatic cancer may occasionally require a simultaneous colon resection. The risks and benefits of this combined procedure are largely unknown. This systematic review aimed to assess short and long term outcome after pancreatoduodenectomy with colon resection (PD-colon) for pancreatic ductal adenocarcinoma (PDAC). - Methods - A systematic literature search was performed in PubMed, Embase, and the Cochrane Library for studies published between 1994 and 2017 concerning PD-colon for PDAC. - Results - After screening 2038 articles, 5 articles with a total of 181 patients undergoing PD-colon were eligible for inclusion. Included studies showed a relatively low risk of bias. The pooled complication rate was 73% (95% CI 61-84) including a pooled colonic anastomotic leak rate of 5.5%. Pooled mortality was 10% (95% CI 6-15). Pooled mean survival (data from 86 patients) was 18 months (95% CI 13-23) with pooled 3- and 5-year survival of 31% (95% CI 20-72) and 19% (95% CI 6-38). - Conclusion - Based on the available data, PD-colon for PDAC seems to be associated with an increased morbidity and mortality but with survival comparable with standard PD in selected patients. Future large series are needed to allow for better patient selection for PD-colon.